Recent Trends and Outlook in the International Sugar Industry - Muthaiya, C. (Indian Journal of Marketing, 2011)
The Indian sugar industry is the second largest agro-industry located in the rural India. The Indian sugar industry has a turnover of 700 billion per annum and it contributes almost 22.5 billion to the central and state exchequer as tax, cess, and excise duty every year (Source: Ministry of Food, Government of India). It is the second largest agro-processing industry in the country after cotton textiles. With more than 600 operating sugar mills in different parts of the country, Indian sugar industry has been a focal point for socio-economic development in the rural areas. About 50 million sugarcane farmers and a large number of agricultural laborers are involved in sugarcane cultivation and ancillary activities, constituting 7.5% of the rural population. Besides, the industry provides employment to about 2 million skilled/semi skilled workers and others mostly from the rural areas. The Sugar industry is hovering at the beginning of the upturn in the sugar cycle. Uptrend in sugar cycle starts with increased availability of sugar, decline in sugar prices, lower profitability for mill owners, delayed payment to farmers, high sugarcane arrears&thus farmers switch over to other crops resulting in lower cane production. All these factors result in higher sugar prices and again cycle turns around. In 2008-09 SS (Sugar Season), production is expected to fall by 21.5 per cent to 21.2 million tonnes on account of a decline in area under sugarcane cultivation. Sugarcane arrears that started building up since the middle of the 2006-07 SS will have caused farmers to switch to other crops such as wheat and Paddy. The country's sugar production in October - April (2007-08) declined by 4.74% to 24.1 million tones on account of delayed crushing and diversion to gur and khandhsari units, particularly in Uttar Pradesh (UP). The Sugar season runs from October to September. Industry estimates that the final output figure for the whole season could see a drop of nearly 9% from the previous season's 24.1 mt.